Peningkatan Kualitas Sumber Daya Manusia Melalui Pemanfaatan Tanaman Herbal Untuk Kesehatan Di Desa Karang Panggung Bengkulu Tengah - Sunoto, Sunoto; Indraswanti, Bertha Iin Esti; Hermanto, Bambang Agoes (Kreativasi : Journal of Community Empowerment, 2025)
In the development process, human resource is crucial determinant. Not only about the quantity, it also the quality. HDI is an indicator of human development which form of tree composite index; education index, healthy index, and standard of living index. To increase the HDI, one of the ways is to improve the healthy index by create programs of healthy development that could be increase the number of expecting life. The awareness of quality of life is important in a society. The herbal plants can be source of society healthy. The herbal plants usually to produce “jamu”, is a traditional medicine in Indonesia. It can be preventive or curative treatment for healthy. In Karang Panggung Village, there are many herbal plants but the people usually just for cooking or to sell original form. So, how to create something new must introduced to them. Not only for healthy, but it can be created value added.